Innovative approaches to the strategic management of the regional economy - Moskalenko, V. (Університет «КРОК», 2017)
The article explores the role of forecasting in the regional planning system and new approaches to strategic planning at the regional level, in particular roadmapping
Keywords: forecasting; strategic planning; roadmapping